The Regional and their applications in Geography and its fields between illusion and truth - Sha’aban, Asst. Prof. Huda Khalid (Thi Qar Arts Journal, 2023)
The regions are the product of regional studies that researchers exchange in their studies in the natural and human sciences of geography, where the applications of the regions have extended in many sciences, such as sociology, economics, soil, planning, soil, plant environmental sciences until a special science of the region emerged called (regional science). The idea of division entered the field of social planning such as planning and development regions with the aim of achieving regional justice between cities. The applications of the regions varied among researchers according to the goal and need for them. They were distinguished by the stability of the natural regions and the mobility of the human regions. To achieve this, the research relied on the descriptive and analytical methods as well as the desk survey. Received 6/10/2023 , Accepted 26/11/2023 , Published 31/12/2023